Intracuff lidocaine 2% for prevention of postoperative cough and sore throat - Mokhtar Mahmoud Younes (Wolters Kluwer Medknow Publications, 2018)
Background Tracheal intubation results in an alteration of the laryngeal mucosa. Coughing during emergence from general anesthesia is a common clinical problem. Inflation of the endotracheal tube cuff with lidocaine would create a reservoir of local anesthetic, which might diffuse across the cuff membrane to anesthetize the mucosa and attenuate stimulation during tracheal extubation. Aim To evaluate the efficacy of intracuff lidocaine 2% for the prevention of postoperative cough and sore throat. Patients and methods This prospective, randomized, controlled, double-blind study included 80 healthy patients scheduled for elective surgery of less than 2 h under general anesthesia with orotracheal intubation. These 80 patients were randomized through a computer-generated and sealed opaque envelope method into four equal groups, with 20 patients each. After induction of general anesthesia and tracheal intubation, the tracheal tube cuff was filled with 2 ml of 2% lidocaine solution (40 mg) or 0.9% saline. Twenty minutes before extubation, the participants received 1.5 mg/kg intravenous lignocaine or saline. In this way, four groups were formed: lidocaine cuff-lidocaine group (lidocaine in cuff and lidocaine intravenous), lidocaine cuff-saline group (lidocaine in the cuff and saline intravenous); saline cuff-lidocaine group (saline in cuff and lidocaine intravenous), and saline cuff-saline group (saline in cuff and saline intravenous). The primary outcome was the incidence of coughing at extubation. The secondary outcomes were sore throat scores and hemodynamic change. The incidence and severity of sore throat was recorded at 15, 60 min, and 24 h after extubation. Hemodynamic change was assessed at before induction (baseline), 5-min interval after induction, at intubation, 10 min after intubation, 10 min before extubation, at extubation, and 10 min after extubation. Result There was a statistically significant reduction of postoperative cough and sore throat in lidocaine cuff groups in comparison to saline cuff groups. Intravenous lidocaine was not effective to reduce either cough or sore throat severity. However, there was no significant difference among all groups regarding hemodynamic change. Conclusion Intracuff lidocaine 2% reduces incidence of cough and the severity of postoperative sore throat in surgery of less than 120 min. Intravenous lidocaine was not effective to reduce either cough or sore throat severity. There was no significant difference among all groups regarding hemodynamic change.